Publishing and Polar Exploration - Leane, E (The Royal Society of Tasmania, 2018)
'It seems a pity, but I do not think I can write more': so the dying Robert F. Scottscrawled into his Antarctic diary, before signing off for the last time. It might seemsurprising that for Scott- starving, freezing, exhausted and surrounded by his dead ornear-dead companions in a small tent on an Antarctic ice shelf- the 'pity' of his situationlay in his inability to write. While this concluding statement could simply be read as theBritish explorer's understated way of signalling his knowledge of his own impendingdeath, this was not the only time that Scott had connected survival with writing. His'Message to the Public', written earlier into the back of his diary, included the now-famousline, 'Had we lived, I should have had a tale to tell . that would have stirredthe heart of every Englishman'. Again, the main benefit of living, as Scott frames it, isto be able to tell one's story. His words are a salient reminder that, in polar explorationconducted remote from human witnesses, writing (and, eventually, publishing) is just asimportant as action.